Computer-aided mobility analysis of parallel mechanisms. (June 2020) - Zhu, Xiaorong; Shen, Huiping; Wu, Chengqi; Chablat, Damien; Yang, Tingli
Highlights: Mobility analysis includes the number of DOF and the position and orientation of a PM. A complete digital information model for topological structures of a PM is proposed. The algorithmic procedures and software for an automatic mobility analysis are presented. Abstract: To determine mobility properties is one of the most challenging issue in the analysis and synthesis of parallel manipulators (PMs). However, currently, the most used methods mainly rely on experiences and manual analysis, which led to inefficient implementation. The motivation of this paper is to present an automatic mobility analysis algorithm and software package for the researchers and designers with an effective and practical means. According to the topological design theory of PMs based on position and orientation characteristic (POC) equations, this paper proposes a set of computer algorithmic rules and procedures for automated mobility analysis of PMs in the most user-friendly and efficient way. Firstly, a complete digital information model for topological structures which has a mapping relationship with the POC of a PM is proposed. This model not only describes the dimension of the motion outputs, but also includes the mapping relationship between the output orientation and the axes of the kinematic joints. Secondly, algorithmic rules are established that convert the union and intersection operations of POC into binary logical operations and then the detailed algorithmic procedures for an automatic mobility analysis are presented. In what follows, a corresponding software for automatic mobility analysis is described. The software package is equipped with a GUI that facilitates the input and allows the visualization of the results. Finally, four typical examples are provided to show the effectiveness of the software package for most of parallel mechanisms (not including some paradoxical mechanisms).